Effect of bonding agents used as lubricants on the color stability of composite restorations - Badeeb, Bayan (Tufts University Tisch Library, 2025)
Thesis (M.S.)--Tufts University, 2025.; Submitted to the Dept. of Posthodontics.; Advisor: Carlos Kose Junior.; Committee: Aikaterini Papathanasiou, Gustavo Mahn Arteaga, and Sarah Ellen Pagni.; Keyword: Dentistry.